Penyelesaian Pertanggungjawaban Kelalaian Pihak Kontraktor Dalam Pembangunan Villa : Studi Putusan Nomor 47/PDT.G/2021/PN.MTR - Mutiara Rizkiandini Putri; Djumardin Djumardin (Fakultas Hukum Universitas Mataram, 2022)
This research aims to find out the form of liability of the service provider for the development failure and legal consequences of service provider which was acted default in construction agreement due to not conducting the obligation which was written in the letter of agreement. The method of this research is normative legal research using statute, conceptual, and case approaches. In the legal relationship between plaintiff and defendant show that good faith to accomplish the building in 100% in 12 months and 10 days by following the construction agreement.